2020
DOI: 10.2337/db19-0920
|View full text |Cite
|
Sign up to set email alerts
|

Branched-Chain Amino Acids Exacerbate Obesity-Related Hepatic Glucose and Lipid Metabolic Disorders via Attenuating Akt2 Signaling

Abstract: Branched chain amino acids (BCAAs) are associated with the progression of obesity-related metabolic disorders, including type 2 diabetes and nonalcoholic fatty liver disease. However, whether BCAAs disrupt the homeostasis of hepatic glucose and lipid metabolism remains unknown. In this study, we observed that BCAAs supplementation significantly reduced high-fat (HF) diet-induced hepatic lipid accumulation while increasing the plasma lipid levels and promoting muscular and renal lipid accumulation. Further stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 50 publications
0
55
1
Order By: Relevance
“…Thus, the increased postprandial uptake of BCAA after two months of HFHS feeding could respond to the increased circulating concentration of BCAA already observed in obese hyperinsulinemic mini-pigs [ 5 , 52 ]. Indeed, high insulin levels have been shown to enhance BCAA uptake in the liver of obese rats [ 53 ] and promote further severe liver insulin resistance by the attenuation of Akt2 signaling via mTORC1- and mTORC2-dependent pathways [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the increased postprandial uptake of BCAA after two months of HFHS feeding could respond to the increased circulating concentration of BCAA already observed in obese hyperinsulinemic mini-pigs [ 5 , 52 ]. Indeed, high insulin levels have been shown to enhance BCAA uptake in the liver of obese rats [ 53 ] and promote further severe liver insulin resistance by the attenuation of Akt2 signaling via mTORC1- and mTORC2-dependent pathways [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high BCAT1 expression possess a lower overall survival than those with low BCAT1 expression (103). Leucine and its conversion product α-ketoisocaproate (KIC) are sensed by leucyl-tRNA synthase (LeuRS) (Figure 1) (104). LeuRS acts as a GTPase-activating protein (GAP) for RagD GTPase activating mTORC1 (105).…”
Section: Bcaasmentioning
confidence: 99%
“…LeuRS acts as a GTPase-activating protein (GAP) for RagD GTPase activating mTORC1 (105). In high fat-diet (HFD)-treated diet-induced obesity (DIO) mice, BCAA supplementation increased hepatic BCAA and BCKA levels and induced severe hepatic insulin resistance (IR) (104).…”
Section: Bcaasmentioning
confidence: 99%
“…The decrease of BCAAs in ALD also indicates that alcohol may cause a deficiency of nutrient intake (19). Zhao et al (25) found that BCAAs exacerbated obesity-related hepatic glucose and lipid metabolic disorders through attenuating Akt2 signaling. Tedesco et al (26) found that enriched in BCAAs reverted these molecular defects and mitochondrial dysfunction, suggesting that the mitochondrial integrity obtained with the amino acid supplementation could be mediated through a Sirt1-eNOS-mTOR pathway.…”
Section: Differential Liver Amino Acid In Ald Ratsmentioning
confidence: 99%